Identification and Expression Analysis of BURP Domain-Containing Genes in Medicago truncatula - Li, Yuan; Chen, Xue; Chen, Zhu; Cai, Ronghao; Zhang, Hongmei; Xiang, Yan (Frontiers in Plant Science, 2016)
Abstract: BURP domain-containing proteins belong to a newly identified protein class that is unique to plants and plays an important role in plant development and metabolism. Although systematic characterization of BURP domain-containing proteins have been carried out in many species, such as rice, poplar and maize, little is known about BURP domain-containing proteins in Medicago. In this study, multiple bioinformatics approaches were employed to identify all the members of BURP family genes in Medicago. A complete set of 39 BURP family genes were identified. These genes have diverse structures and were distributed on chromosome 1 to 8 except 7. According to phylogenetic analysis, these BURP family genes could be classified into eight classes. Motif and exon-intron organization, stress-related cis-elements in promoter regions and microarray analysis of MtBURPs were also performed. Furthermore, transcript level analysis of MtBURP genes in response to drought stress revealed that all of the 39 BURP genes were regulated by drought stress. The results of this study reveal a comprehensive overview of the Medicago BURP gene family and provide the first step towards the selection of MtBURP genes for cloning and functional analysis of the BURP gene family in Medicago truncatula .